Sistem Informasi Geografis Gereja Katolik Pada Wilayah Keuskupan Atambua Berbasis Web - Yohanes R. I. Manek; Patrisius Batarius; Emerensiana Ngaga (Sekawan Institut, 2023)
Atambua Diocese is a diocese centered on the Belu district, its territory is divided into 3 districts which include Belu, Malaka, and North Central Timor districts. The spread of churches in remote areas makes it difficult for people to find locations and information on church activities, number of people, mass schedules and leaders because information about churches is not yet available. Geographic Information System is used to solve the problems experienced in Atambua Diocese. This system can provide information related to the Catholic church in the Diocese of Atambua based on Web-GIS. This study uses the Waterfall method which approaches systematically and sequentially starting from the analysis, design, coding, testing, and maintenance stages. This Web-GIS-based system was developed using the PHP programming language and MySQL database. This application produces a Web-GIS that can provide information and the location of the Catholic church in the Atambua Diocese area.